BIMBINGAN ISLAM DALAM MENGATASI KESEPIAN KEPADA LANSIA DI LEMBAGA KESEJAHTERAAN SOSIAL (LKS) PONDOK LANSIA GIMBAR ALAM PRINGSEWU - Noffiyanti; Alawiyah, Desi; Lina Kurniatun; Abdul Syukur (Universitas Islam Ahmad Dahlan, 2024)
Elderly is the final stage in human life which is characterized by a process of decreasing abilities, both physical and psychological. As is the case in LKS Pondok Lansia Gimbar Alam Pringsewu which has psychological problems for the elderly, namely loneliness. Loneliness in the elderly is caused by the need to have close relationships with the closest family not being fulfilled. This research aims to examine the process of implementing Islamic guidance in overcoming loneliness in the elderly LKS Pondok Lansia Gimbar Alam Pringsewu. This research is qualitative research, with field research and qualitative descriptive research. Determining informants in this research used the snawball sampling technique. Primary data sources numbered 6 people, consisting of 1 religious guide (ustads), 3 elderly people and 2 informants. The collection methods in this research used observation, interviews and documentation. Data analysis techniques use, data reduction, data presentation and drawing conclusions. Based on the results of data analysis, it was found that the process of implementing Islamic guidance had a positive impact on the elderly. Carrying out this activity means that the elderly at LKS Pondok Lansia Gimbar Alam Pringsewu are not lost in sadness and can prevent the elderly from feeling lonely because when Islamic guidance takes place, interaction between the elderly is created so that the need for close relationships is fulfilled.